Genotype × Environment Effects in Three Wild Relatives of Sorghum From Australia - Harry Myrans; Dinithi Chithrarachchige; Robert J. Henry; Sally Norton; Roslyn M. Gleadow (Plant-Environment Interactions)
ABSTRACT Endemic wild Sorghum species are prevalent across northern Australia and could be useful for crop improvement; however, few studies have been done to quantify the phenotypic diversity of this tertiary gene pool. We aimed to assess the interactive effects of genotype and water availability in three wild Sorghum species native to northern Australia and compare these to domesticated sorghum (Sorghum bicolor). Two accessions of wild Sorghum plumosum, Sorghum stipoideum, and Sorghum timorense, sourced from more and less arid regions, were grown alongside a S. bicolor line under well‐watered or drought conditions for 4 weeks. We measured biomass, root:shoot ratio, chlorophyll a:b ratio, and concentrations of chlorophyll. The concentration of phenolics and cyanogenic glucosides were also measured to see if there were any differences in the concentration of specialized metabolites, as this is of particular importance for grazing. Low soil moisture (“drought”) significantly impacted the biomass, root:shoot ratio, and chemical composition of S. bicolor, but the effects on the wild accessions were minimal and mostly not significant. This is potentially a consequence of their adaptation to harsh conditions in northern Australia. In each of the wild study species, genotype effects (i.e., between accessions) were greater than treatment effects, indicating intraspecific diversity. Wild Sorghum is a potential source of novel traits that could be helpful in further enhancing the ability of S. bicolor to tolerate hot and dry conditions. Further research into traits conferring drought tolerance in Sorghum without compromising yield is needed.